Synthesis, thermophysical properties and COSMO-RS study of DBU based protic ionic liquids - Wilfred, Cecilia (2017)
In the present work, a new series of DBU based protic ionic liquids has been synthesized. The anions were generated from acetic acid, trifluoro acetic acid, methane sulfonic acid and trifluoro methanesulfonic acid. The obtained [DBU][Ac], [DBU][Tfa], [DBU][Msa] and [DBU][Tfmsa] ionic liquids were characterized by 1H NMR and 13C NMR.